2008
DOI: 10.1111/j.1348-0421.2008.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on diarrheagenic Escherichia coli isolated from children with diarrhea in Myanmar

Abstract: invasion-associated locus of the invasion plasmid found in EIEC; lt, heat-labile enterotoxin; NB, nutrient broth; PCR, polymerase chain reaction; pCVD, representative plasmid of EAEC; SDS, sodium dodecyl sulfate; SSC, standard saline citrate; stI, heat-stable enterotoxin I; stII, heat-stable enterotoxin II; Stx1, shiga-like toxin 1; Stx2, shiga-like toxin 2; UV, ultraviolet.Key words children, diarrhea, E. coli, Myanmar. ABSTRACTEscherichia coli isolates from 217 children in Myanmar with diarrhea were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…34,35 Previous studies have shown a certain degree of homogeneity for the presence of virulence factors within STEC serotypes. 36 The present study showed that stx 1 was significantly more frequent in isolates from O157 and non-O157 serotypes, followed by stx 2 and none of the strains lack either stx 1 or stx 2 . ehxA was observed to be frequent between isolates from O157 serotypes, but completely absent in non-O157 serotypes.…”
supporting
confidence: 48%
“…34,35 Previous studies have shown a certain degree of homogeneity for the presence of virulence factors within STEC serotypes. 36 The present study showed that stx 1 was significantly more frequent in isolates from O157 and non-O157 serotypes, followed by stx 2 and none of the strains lack either stx 1 or stx 2 . ehxA was observed to be frequent between isolates from O157 serotypes, but completely absent in non-O157 serotypes.…”
supporting
confidence: 48%
“…In recent years, EAEC has emerged as diarrhoeal agent causing acute and chronic diarrhea in all age groups though it was once known to infect primarily newborns and immunocompromised patients [ 4 ]. Studies conducted in Mexico, Bolivia, Nicaragua, and Myanmar found that EAEC was the most common among all the DEC pathotypes [ 14 , 26 28 ]. On the contrary, in our study, EPEC was the most common, similar to the findings of the studies conducted in Israel, Norway [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of O-serogroup was performed using a commercially available Oserogrouping Kit (Denka Seiken, Tokyo, Japan) (Takahashi et al, 2008). The Flagellar phase inversion was carried out using the standard Craigie tube technique by passage through semi-solid agar containing the appropriate flagellar antis era (Davies and Wray, 1997).…”
Section: Somatic and Flagella Serotypingmentioning
confidence: 99%